A Highly Selective GSK-3β Inhibitor CHIR99021 Promotes Osteogenesis by Activating Canonical and Autophagy-Mediated Wnt Signaling - Wang, Bo; Khan, Saima; Wang, Pengtao; Wang, Xiaofang; Liu, Yangxi; Chen, Jingjing; Tu, Xiaolin (Frontiers in Endocrinology, 2022)
The discovery and application of small molecule drugs is one of the practical strategies of safe osteogenic drugs. The small molecule CHIR99021 (C91) is a highly specific, safe, and most effective GSK-3β Inhibitor. This study found that it efficiently activates the canonical Wnt signaling of bone marrow stromal cell line ST2 and promotes osteoblast differentiation and mineralization. C91 increases the production and biochemical activity of osteoblast marker alkaline phosphatase, the expression of osteoblast marker genes Alpl, Bglap, Runx2, and Sp7, and the formation of bone nodules. Triptonide is a transcription inhibitor of Wnt target gene, which diminishes C91-induced osteoblast differentiation in a dose-dependent manner. At the same time, C91 also induces autophagy through autophagosome formation and conversion of autophagy biomarker LC-3Ⅰinto LC-3Ⅱ. Autophagy inhibitor 3MA partially reduces C91-induced osteoblast differentiation and mineralization; Autophagy inducer Rapamycin increases the expression of β-catenin to promote osteogenic differentiation, but cannot alleviate the inhibition of Triptonide on C91-induced osteogenic differentiation, indicating the crosstalk of canonical Wnt signaling and autophagy regulates C91-induced osteoblast differentiation. Furthermore, in order to simulate the in vivo detection of C91 in osteogenesis process, we established a C91 slow-release hydrogel by our newly established polycaprolactone and cell-integrated 3D printing system (PCCI3D). The sustained release C91 promotes the differentiation and mineralization of ST2 cells. C91 can also enhance the proliferative activity of ST2 cells. The release rate of C91 is 83%, and the release rate of C91 from hydrogel gradually decreases within 7 days. During this period, cell viability is maintained at 96.4%. Therefore, the small molecule Wnt agonist C91 promotes osteogenesis through autophagy and the caonical Wnt signaling pathway, which is suitable for translational application.